Psikologi Tokoh Utama Dalam Novel Lampuki Karya Arafat Nur - Ira Fatani; Rasyimah; Safriandi (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the psychology of the main character in the novel Lampuki by Arafat Nur. In the aspects of id, ego, and superego in the main character contained in the novel Lampuki by Arafat Nur. The study uses a  qualitative approach and this type of approach is descriptive qualitative. The data of this study are excerpts of paragraphs, dialogues, and sentences that contain the psychology of the main character in the novel Lampuki by Arafat Nur. The data collection technique for this study is the reading and note-taking technique in this study. Based on the research results, a total of  80 data were obtained. 20 data were found for id, 47 data were found for ego and 13 data were found for superego.